Specificity of the Methodological System in Teaching Russian Language - Khudoykulovna, Mukumova Gulnara (European Journal of Life Safety and Stability (2660-9630), 2021)
Among the "world" languages as a means of international communication, the role of the Russian language is exceptionally great. The Russian language is rightfully considered the world language, which is due to the entire course of the socio-political, economic, scientific, technical and cultural development of mankind in the XX XXI centuries. The role of the Russian language as an international language is also great for the exchange of scientific information. This is primarily due to the "international" nature of modern science and the unprecedented pace of its development. Nowadays, it is important that every student speaks fluent Russian. In this regard, it is important to use new methods of teaching the Russian language. The article describes the methodology of teaching the Russian language in the world experience.